Research on CM multi-granular resource access control strategy based on graph theory. (16th August 2011) - Li, Chunquan; Shang, Yuling; Hu, Chunyang; Kuang, Xiaole; Zhu, Panfeng
In this paper, the structure of the CM access control is analysed. The multi-granular resource access control model (MGAC) is proposed on the basis of attribute-based access control. The solving algorithm of MGAC digraph is investigated by considering the simplest authority overlay graphic and the authority migration path. In the meantime, MGAC algorithm is illustrated by numerical experiments. The results show that the method has higher efficiency, and the algorithm can fits the access control requirements of single-granular and multi-granular resource in CM.